(untitled) (المجلة الدولية للبحوث العلمية, 2024)
The objective was to understand the individual strengths and needs of healthcare professionals in healthcare provision at Boguila health facility, in Central African Republic. A descriptive design was used for this study. Data were collected using a structured questionnaire; 19 Nurses-Aids were interviewed (86% sample). The data were double entered, cleaned, and analyzed using excel. The problem this study aims to address is that in the past 7 years the medical staff at Boguila health center did not receive training for continuous professional development due to insecurity which caused a phase out of the international staff who were in charge of this task. 75% of the nursing staff in health center by which the survey has been conducted have between six and eight years of working experience suggested to have continuous professional development in terms of make the daily report, obstructed labor, management of patients with TB/HIV, pediatric dose calculations, use of computer and data management, anatomy and physiology, care of a pregnant woman at work, and sexual gender based violence management. They show their strength in Out Patient Department (OPD) consultations, triage of patients, IEC provision, treatment for malaria, and caring for patients affected by malnutrition.